2012
DOI: 10.4236/jwarp.2012.411114
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level Approach of the Ecotoxicological Impact of a Combined Sewer Overflow on a Peri-Urban Stream

Abstract: In periurban zones, urban wet weather discharges have been recognized as the most significant vector of pollution in aquatic environments. The discharge of this water without treatment into the aquatic environment could present an ecotoxicological risk for biocenosis. The aim of the INVASION project is to assess the potential ecotoxicological impact of a combined sewer overflow (CSO) on a peri-urban stream. A comparative study between upstream and downstream areas of the CSO allowed observing significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Much research has been conducted by the various teams participating at all levels of study: the characterisation of precipitations (Emmanuel et al 2012;Renard et al 2012;Lepioufle et al 2012), microbiology (Badin et al 2012;Maazouzi et al 2011) and the pollution of receiving environments (Becouze et al 2011;Becouze-Lareure 2012), and the hydrological modelling of the consequences of builtup areas Kouyi et al 2011). New themes include study of local effects on pluviometry, such as those related to urban environments (roughness, island of urban heat, pollution, albedo, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been conducted by the various teams participating at all levels of study: the characterisation of precipitations (Emmanuel et al 2012;Renard et al 2012;Lepioufle et al 2012), microbiology (Badin et al 2012;Maazouzi et al 2011) and the pollution of receiving environments (Becouze et al 2011;Becouze-Lareure 2012), and the hydrological modelling of the consequences of builtup areas Kouyi et al 2011). New themes include study of local effects on pluviometry, such as those related to urban environments (roughness, island of urban heat, pollution, albedo, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical approach highlighted the critical nature of some substances (Ptot, Al, total residual chlorine, Cr, Cu, pyrene, NH 4 + -N, Pb, and Zn). Becouze-Lareure [19] evaluated the ecotoxicological impact of a combined sewer overflow (CSO) on the Chaudanne, a periurban stream situated in a peri-urban drainage basin in the Lyon area of France. Not only chemical analysis methods, but also the ecotoxicity risk assessment method of four kinds of aquatic organisms were used to compare the impact of upstream and downstream of rivers evaluated the CSOs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the four organisms used to assess the CSOs, only two aquatic organisms showed chronic toxic effects. Combining the results of chemical analysis, it is reported that the CSO might influences the ecosystem of the watershed [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous focused studies have been made of the hazards (physical phenomena of a given nature, intensity and occurrence) linked to these risks in the Lyon area (Kouyi et al 2011;Becouze-Lareure 2012), publications on the vulnerability of Greater Lyon are rare. In fact, after being based historically on the control of hazards, risk management has recently addressed Step-by-step procedure for a territorial vulnerability clustering process.…”
Section: Introductionmentioning
confidence: 99%